Residual, Differential, and Absolute Urban Ground Rents and Their Cyclical Fluctuations - Pribram, Karl (Econometrica, 1940)
THE OBJECTIONS which have been raised against the fundamentals of the value theory of the classical school of economics hardly ever went so far as to affect the principle upon which the Ricardian explanation of land values was based, viz., the idea that the value of land is not to be explained in terms of cost, but in terms of a residual rent. This idea when developed into its consequences has even facilitated the insight into many value phenomena other than land values. However neither Ricardo nor his postclassical followers ever attempted thoroughly to examine the question whether and with what modifications the residual rent concept can be used in interpreting the economic phenomena presented by the existence of urban land values. To my knowledge the first author who undertook the task of establishing a consistent theory of the urban ground rent was the Austrian economist F. von Wieser.' Wieser emphasized an important distinction obtaining between the agricultural ground rent and its urban counterpart with respect to the relations between the factors which are instrumental in producing the differential returns: the former is due to the fact that, owing to increased demand for farm products, agricultural production may be profitable also at increased costs, with the result that a surplus profit accrues to those farmers whose production is privileged by lower costs. On the other hand, according to the Wieserian theory, the residual rent of urban sites is largely independent of differences in costs of construction; it is due to differences in the demand for the services rendered by different real-estate properties and, consequently, to differences in the prices paid for such services. Von Wieser has specified his theory by distinguishing within each locality a range of housing markets which differ according to the situation of the sites. The tendency to exploit the privileged sites to the fullest possible degree is reflected in the process of intensifying the utilization of land of this type both horizontally and vertically. The larger the portion of the lot which is utilized for dwelling and renting purposes and. in addition. the larger the number of dwellinL;s and premises * Paper presented at Colorado Springs, July 26 and 27, 1939, before Cowles Commission Fifth Annual Research Conference on Economics and Statistics, under title of Some Dynamic Aspects of the Urban Ground Rent. 1 v. Wieser, Theorie der gesellschaftlichen Wirtschaft in Grundriss der Sozialdkonomie, 1, p. 362.